Increased Survival and Partly Preserved Cognition in a Patient With ACO2-Related Disease Secondary to a Novel Variant. (August 2017) - Srivastava, Siddharth; Gubbels, Cynthia S.; Dies, Kira; Fulton, Anne; Yu, Timothy; Sahin, Mustafa
ACO2 encodes aconitase 2, catalyzing the second step of the tricarboxylic acid. To date, there are only 6 reported families with 5 unique ACO2 mutations. Affected individuals can develop intellectual disability, epilepsy, brain atrophy, hypotonia, ataxia, optic atrophy, and retinal degeneration. Here, we report an 18-year-old boy with a novel ACO2 variant discovered on whole-exome sequencing. He presented with childhood-onset ataxia, impaired self-help skills comparable to severe-profound intellectual disability, intractable epilepsy, cerebellar atrophy, peripheral neuropathy, optic atrophy, and pigmentary retinopathy. His variant is the sixth unique ACO2 mutation. In addition, compared to mild cases (isolated optic atrophy) and severe cases (infantile death), our patient may be moderately affected, evident by increased survival and some preserved cognition (ability to speak full sentences and follow commands), which is a novel presentation. This case expands the disease spectrum to include increased survival with partly spared cognition.